Penerapan Metode Profil Matching Dalam Pemilihan Tanah Lahan Pertanian - Masuri, Masuri; Permadi, Dika Firman; Widyassari, Adhika Pramita (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2025)
Abstract The selection of agricultural land that matches crop characteristics is a crucial factor in improving productivity and sustainability in Indonesia's agricultural sector. This study aims to develop and implement the Profile Matching method in a decision support system to provide optimal recommendations for agricultural land selection. The Profile Matching method is used because it systematically and objectively compares the ideal crop requirements with the actual land conditions. This research involves identifying land criteria and sub-criteria such as soil texture, pH, nutrient content, rainfall, temperature, and topography, which are then analyzed using gap calculation stages, weighting, and grouping into core and secondary factors. The results show that the Profile Matching method is effective in ranking land suitability, thereby assisting farmers and policymakers in determining the best land for specific crops. The developed system provides a data-driven solution that minimizes subjectivity in decision-making and supports efforts to improve efficiency and productivity in sustainable agriculture.